Strategic planning to optimize exploration in junior mining companies (exploration) listed in the Lima Stock Exchange - Arhuata Cachicatari, Percy (2022)
The research is about how should be explorations managed in the exploration junior mining companies with foreign capital established in Peru, considering of strategies that they used in the last three decades to achieve success. Strategic planning is used for the exploration phase, integrating exploration and acquisition strategies in a decision tree, based on experiences of three junior mining companies listed on the Lima Stock Exchange that were successful with their mining projects, these will be references so that other similar companies implement strategic planning and can improve management of their explorations to increase the profitability of their shareholders, it’s not enough to have good projects, because if they do not know how to manage them they do not advance, or else could be obtained feedback from results to correct and guide decisions to increase the chances of success. The information used for this investigation was diverse management documentation and technical information presented by mentioned companies in the Lima and Toronto stock markets, available in the Electronic Document Analysis and Retrieval System (SEDAR), an official site that provides access through of your website.